Free Radical Inhibition Using a Water-Soluble Curcumin Complex, NDS27: Mechanism Study Using EPR, Chemiluminescence, and Docking - Ange Mouithys-Mickalad; Koffi Senam Etsè; Thierry Franck; Justine Ceusters; Ariane Niesten; Hélène Graide; Ginette Deby-Dupont; Charlotte Sandersen; Didier Serteyn (Antioxidants, 2024)
There is a growing interest in the use of natural compounds to tackle inflammatory diseases and cancers. However, most of them face the bioavailability and solubility challenges to reaching cellular compartments and exert their potential biological effects. Polyphenols belong to that class of molecules, and numerous efforts have been made to improve and overcome these problems. Curcumin is widely studied for its antioxidant and anti-inflammatory properties as well as its use as an anticancer agent. However, its poor solubility and bioavailability are often a source of concern with disappointing or unexpected results in cellular models or in vivo, which limits the clinical use of curcumin as such. Beside nanoparticles and liposomes, cyclodextrins are one of the best candidates to improve the solubility of these molecules. We have used lysine and cyclodextrin to form a water-soluble curcumin complex, named NDS27, in which potential anti-inflammatory effects were demonstrated in cellular and in vivo models. Herein, we investigated for the first time its direct free radicals scavenging activity on DPPH/ABTS assays as well as on hydroxyl, superoxide anion, and peroxyl radical species. The ability of NDS27 to quench singlet oxygen, produced by rose bengal photosensitization, was studied, as was the inhibiting effect on the enzyme-catalyzed oxidation of the co-substrate, luminol analog (L012), using horseradish peroxidase (HRP)/hydrogen peroxide (H2O2) system. Finally, docking was performed to study the behavior of NDS27 in the active site of the peroxidase enzyme.